Editor’s Foreword - Yeo, Asten (Trinity Student Medical Journal, 2024)
I am pleased to say that this issue of the TSMJ is one of the most diverse issues of the TSMJ thus far, not only because of the range of article types, but from the range of contributing authors from the various health science disciplines here in Trinity. Though some might assume that we only publish articles written by medical students, the TSMJ remains an inclusive open-access student journal covering all fields related to medicine and biomedical science, and it is encouraging to see a return to such. While the COVID-19 pandemic has certainly made original clinical research difficult for students, we have nonetheless continued to find ways to contribute. In this issue, we featured systematic reviews looking at the role of prophylactic vaccination against shingles in autoimmune patients undergoing biologic therapy and whether antibiotics or surgery should be first-line for acute uncomplicated appendicitis. Also featured is a brilliant full-cycle clinical improvement project report on the use of the ISBAR3 handover technique in a tertiary paediatric centre, which goes to show the value that medical students can have in contributing to clinical practice outside of primary research. For those interested in public health or immunopathology, we also have two detailed reviews looking at maternal mortality in Sweden, India, and Rwanda and at the role of Th17 lineage cells in the pathogenesis of COVID-19. I am also pleased to see the return of the interview article which has been absent from the TSMJ for some time. Interviews are great for providing a concise and often personal view of hot topics in medicine. In this issue, our staff writers spoke to Anna Rafferty from Johnson & Johnson about their undergraduate women in STEM programme and Dr Ian Fraser—consultant radiation oncologist at the Hermitage Medical Clinic—about CyberKnife, the first fully robotic radiotherapy device. While original research and reviews nonetheless remain the focus of TSMJ, we are also proud to present perspectives written by our staff writers on recent and topical events, such as our cover piece on newly approved anti-amyloid drug aducanumab, or our other fantastic piece on emerging infectious diseases. To end, I would like to thank the School of Medicine of Trinity College Dublin and our advisors for supporting the TSMJ and ensuring that it meets high editorial standards. Many thanks to the TCD Student Open Access Project, which has supported the online publication of the TSMJ, as well as other student open-access journals from various faculties around Trinity. I would also like to thank our sponsors from Johnson and Johnson, the Medical Protection Society, and the Trinity Association and Trust. Without their generosity, it would not be possible to print, produce, and publish, either in print or online. Last, but not least, I would like to express my deepest gratitude and appreciation towards the whole TSMJ committee. I am incredibly grateful to have been able to work—with and for—all the talented directors, editors and reviewers who have so graciously volunteered with us this year. To our directors: your time and effort have gone towards not only producing this volume but also the myriad background tasks that keep the TSMJ running, from organising events and journal clubs to running our social media accounts and website. As one of the largest committees in recent years (with an equally large agenda), this must have been no easy feat. A special commendation should also go out to our Media Director, Rachel Chen, who was also responsible for the wonderful artwork that adorns the cover of this issue. As for our editors and reviewers, you have been—now and always—the driving force of the TSMJ. As well as our appreciation, you have also my sincerest apologies, for the sheer size of this year’s volume should elucidate just how much has been edited, reviewed and formatted over countless drafts. Thank you for the many hours spent reading and re-reading manuscripts, figuring out how to best showcase the work of the authors. I hope that this volume is as much a pleasure to read as it was for us to work on, and that Volume 22 stands as a testament to what can be achieved from the cumulative talent and hard work of all the brilliant medicine and health science students that we have here in Trinity. I look forward to what the next committee has to offer.